World development indicators - ebrary, Inc. (Washington, D.C. : The World Bank, 2004)
The WDR focuses on basic services, particularly health, education, water, and sanitation, seeking ways of making them work for poor people. Services work when they include all the people, when girls are encouraged to go to school, when pupils and parents participate in the schooling process, when communities take charge of their own sanitation. They work when societies cacurtailcorruption$1 (Bwhich hurts poor people more than it hurts the better off$1 (Bparticularly when it hits basic health services, which poor people need desperately.In short, this year$1 (Bs WDR is central to the World Bank$1 (Bs two-pronged strategy for development$1 (Binvesting in and empowering people, and improving the climate for investment.s
Description based on: 1997.
Includes bibliographical references and index.
rpm 27/09/2016
Ref
Keywords: Economic history; Economic history -- 1990- -- Statistics -- Periodicals; Economic development; Economic development -- Statistics -- Periodicals; Economic indicators; Economic indicators -- Periodicals. .; Social indicators; Developing countries -- Economic conditions -- Statistics; Developing countries -- Social conditions -- Statistics